Core idea、technical architecture and strategic significance of “5G+” system - Kang CAI; Xiaohong LIAO; Hua TAN (Dianxin kexue)
Based on the investigation of digital native evolution and case analysis,the concept framework of “5G+native” was put forward to describe the application scenarios and enterprises highly dependent on 5G high-performance network connection,its core idea was discussed,including link as a service,5G network and digital capability aggregation,embedded 5G,5G network platformization,etc,and the technical system was designed composed of layers:native access capability,native network capability,native service capability and native application scenario,then its strategic significance was described.The main conclusion is that “5G+native” is an important way for 5G to empower the social and economic development deeply.It is a strategic choice for operators to adapt to customer needs for digital transformation,to establish differentiated competitive advantages,and to build a new convergent ecosystem.Therefore,the construction of the technical and business system should be speed up correspondingly.